PENGARUH LITERASI KEUANGAN, LITERASI DIGITAL DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK ONLINE: PENGARUH LITERASI KEUANGAN, LITERASI DIGITAL DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK ONLINE - Wahyuningsih, Roy (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The rapid development of technology has an impact on the pattern of human interaction with technology. So that it provides opportunities for increasing e-commerce in Indonesia. The purpose of this study is to explain whether there is an effect of financial literacy, digital literacy and digital marketing on online product purchasing decisions. The method used in this research is descriptive quantitative method with multiple linear regression. The sample used is a saturated sample of 105 Economics Education students at STKIP PGRI Jombang. Methods of data collection using documentation, questionnaires and interviews. The results of the study are that financial literacy influences online product purchasing decisions; digital literacy influences the decision to purchase online products; digital marketing influences purchasing decisions; financial literacy, digital literacy and digital marketing influence online product purchasing decisions.